Optimal medium and conditions for phytase production by thermophilic bacterium, Anoxybacillus sp. MHW14 - Kanpiengjai, Apinun; Unban, Kridsada; Pratanaphon, Ronachai; Khanongnuch, Chartchai (Food and Applied Bioscience Journal, 2017)
Phytase is one of several enzymes that widely used in feed industry. Feed enzymes are expected to have high thermostability to withstand the high temperature during feed processing. The main purpose of this research was to find out the cheap and optimal medium and condition for production of phytase from a new source of phytase producing bacterium, Anoxybacillus sp. MHW14. The suitable sources of phytic acid, carbon and nitrogen source were selected according to the highest enzyme activity. Rice bran, glucose and ammonium sulfate were found to be the proper components as mentioned, respectively. The least square linear regression according Plackett and Burman design revealed that rice bran and ammonium sulfate were significant positive factors (p<0.05) on phytase production. The quadratic model of central composite design generated reliable predicted equation for maximum phytase activity with optimum rice bran and ammonium sulfate levels of 10.35% and 2.64% (w/v), respectively. The validation of 105% was attained within 0.20 U/mL at 12 h of cultivation at 45°C which confirmed the successful optimization. Moreover, Anoxybacillus sp. MHW14 was capable of producing the enzyme in broad pH (6.0-9.0) at the optimum temperature (45°C) in optimized medium. The unique characters of the bacterium were interesting and it was the first report of phytase from Anoxybacillus sp.